NEW PREMIUM CARS SALES PROMOTION BASED ON THE SYSTEM OF PRE-OWNED CARS SALES TO LOYAL CUSTOMERS - Koryagin, Mark Evgenyevich (Journal of Applied Engineering Science, 2016)
The decline in sales of new cars in Russia leads to the necessity for a more complicated procedure connected with the sale of pre-owned cars. Creating a sequence of premium brand pre-owned cars purchasing and selling will lead to an increase in new car sales and increase customers` loyalty. A mathematical model of the formation of car purchase and transaction chains is proposed. The developed program module allows to create the required number of transaction chains based on customers` requirements. A numerical example demonstrating the effectiveness of the module for the regional car dealerships is provided.